1984
DOI: 10.1042/bj2200529
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-stimulated protein phosphorylation in the pancreatic islet

Abstract: A glucose-dependent phosphorylation of a 68kDa islet-cell protein was observed in islet-cell homogenates. In the presence of [gamma-32P]ATP the protein was phosphorylated only in the presence of alpha-D-glucose; other sugars were ineffective. Activation of the phosphorylation was half-maximal at 0.34 mM-glucose, 7 microM-ATP and 0.3 mM-Mg2+. Although the addition of glucose 6-phosphate in this design did not stimulate phosphorylation of the islet-cell protein, addition of glucose 6-phosphate to the radioactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…We propose, further, that such an inhibition in PP2A activity results in retention of putative exocytotic proteins in their phosphorylated state, which may be necessary for insulin secretion. It is important to point out that several earlier studies from us and others (9,16,17,20,25,30,37,47) have indicated glucose-mediated increases in phosphorylation of several signaling proteins in the islet ␤-cell. Together, our current findings and extant observations in this area indicate rather dual effects by nutrient secretagogues, such as glucose, on the phosphorylation of candidate proteins, namely, stimulation of kinases as well as inhibition of respective phosphoprotein phosphatases.…”
Section: Discussionmentioning
confidence: 99%
“…We propose, further, that such an inhibition in PP2A activity results in retention of putative exocytotic proteins in their phosphorylated state, which may be necessary for insulin secretion. It is important to point out that several earlier studies from us and others (9,16,17,20,25,30,37,47) have indicated glucose-mediated increases in phosphorylation of several signaling proteins in the islet ␤-cell. Together, our current findings and extant observations in this area indicate rather dual effects by nutrient secretagogues, such as glucose, on the phosphorylation of candidate proteins, namely, stimulation of kinases as well as inhibition of respective phosphoprotein phosphatases.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of alloxan has not been firmly established. It has been shown that alloxan inhibits a Ca2+-calmodulindependent protein kinase in extracts of rat islets (Colca et al, 1983). This finding is ofconsiderable interest in view of the growing evidence, reviewed by Harrison et al (1984), implicating protein phosphorylation as a major control mechanism in the regulation of insulin release.…”
Section: Introductionmentioning
confidence: 99%
“…This B-cell selectivity may result from the capacity of the cells to rapidly incorporate both drugs with a short half-life (38)(39)(40) and from the exquisite sensitivity of the cells to the cytotoxic action of these drugs. The alloxan toxicity has been attributed to its direct interactions with islet protein kinase (41) and to its well-known ability to generate highly reactive oxygen radicals (42,43). It is not yet clear whether the destructive effects of streptozotocin are also elicited by free radicals or whether they develop after alkylation of DNA bases (44)(45)(46)(47)(48)(49).…”
Section: Four Different Conditions Leading To B-cell Death In Vitromentioning
confidence: 99%